2019
DOI: 10.1016/j.jsps.2019.04.014
|View full text |Cite
|
Sign up to set email alerts
|

A novel Nanoformulation Development of Eugenol and their treatment in inflammation and periodontitis

Abstract: ObjectiveTo prepare a novel nanoemulsion- Carbopol® 934 gel for Eugenol, in order to prevent the periodontitis.Material and methodsSpontaneous emulsification method was used for the preparation of nanoemulsion in which it contain Eugenol (oil phase), Tween-80 (surfactant), and PEG (co-surfactant). To the development of best nanoemulsion, three-factor three-level central composite design was used in which %oil; %Smix and % water were optimized as independent variables. An optimized–nanoemulsion were converted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 47 publications
1
35
0
Order By: Relevance
“…The contribution of cinnamaldehyde to cinnamon’s antimicrobial properties was reported in other studies [ 81 , 103 ]. Eugenol showed greater antibacterial activity against several oral pathogens in comparison to β-Caryophyllene, although the latter proved to be effective against S. mutans and even more efficient against P. gingivalis , Tannerella forsythia , and Treponema denticola [ 113 , 118 , 119 ]. Linalool and α-Terpineol also proved effective against several periodontopathogens and caries pathogens, but their concentrations in toothpastes or mouthwashes should not exceed 0.04% [ 115 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The contribution of cinnamaldehyde to cinnamon’s antimicrobial properties was reported in other studies [ 81 , 103 ]. Eugenol showed greater antibacterial activity against several oral pathogens in comparison to β-Caryophyllene, although the latter proved to be effective against S. mutans and even more efficient against P. gingivalis , Tannerella forsythia , and Treponema denticola [ 113 , 118 , 119 ]. Linalool and α-Terpineol also proved effective against several periodontopathogens and caries pathogens, but their concentrations in toothpastes or mouthwashes should not exceed 0.04% [ 115 ].…”
Section: Discussionmentioning
confidence: 99%
“…Eugenol nanoemulsion gel exhibited anti-inflammatory activity and analgesic and antibacterial effects, showing promise for the treatment of periodontal disease [ 113 ]. The antibacterial effect of zinc oxide eugenol paste against E. faecalis was confirmed [ 114 ].…”
Section: Main Constituents Of Cinnamomum Spp Amentioning
confidence: 99%
“…The first one is the CEO-NE system with distinctive characteristics such as nanometric size that facilitates its cellular uptake by immune cells, like macrophages, in the inflamed tissues 74 as well as penetration enhancement ability conferred by the surfactant (tween-80 ® ) as one of its components, therefore augmenting the drug cutaneous permeation. [75][76][77][78] The second factor is the permeation pattern of both formulae either controlled (NEG) or sustained (NFs) that has a great influence in decreasing the frequency of dosing at the application site, thence improving the patient compliance for the treatment regimen as well as being cost-effective for prospective commercial production on large scale.…”
Section: In Vivo Anti-inflammatory Activity Against Croton Oil-inducementioning
confidence: 99%
“…Toxicity studies revealed that eugenol-encapsulated poly ε-caprolactone -nanoparticles were safe. 13 Ahmad et al 2018b screened the wound healing effects of eugenol nanoemulsion, formulated using excipients such as Tween-80, Labrasol and water. Further, it was applied topically in rats to study in vivo anti-inflammatory activity and in vitro skin permeation.…”
Section: Introductionmentioning
confidence: 99%
“…Further, it was applied topically in rats to study in vivo anti-inflammatory activity and in vitro skin permeation. 14 Ahmad et al 2019 made eugenol nanoemulsion and characterized by particle size, PDI and transmittance; then formulate eugenol nanoemulsion-gel. Further, they characterized eugenol nanoemulsion-gel for pH, gelling capacity, syringeability, mucoadhesion, irritancy studies and in vitro drug release.…”
Section: Introductionmentioning
confidence: 99%